2014
DOI: 10.5860/crl.75.6.763
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Mentoring Expectations, Activities, and Support in Canadian Academic Libraries

Abstract: Mentoring expectations, activities, and support in Canadian college and university libraries were investigated by surveying 332 recent MLIS graduates, practicing academic librarians, and library administrators. Findings indicate that the presence of a mentoring program will help attract new librarians, retain them, and aid in restructuring efforts that are currently facing many academic libraries. Preferred mentoring activities include those belonging to psychosocial support, career guidance, and role modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Mentoring is a positive factor not only in enhancing retention, but also in supporting promotion. The research points out that employees who have been mentored have higher salaries, get more promotions, and have a higher level of satisfaction in their careers (Harrington and Marshall, 2014). It also enhances scholarly productivity and successful promotion and tenure.…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentoring is a positive factor not only in enhancing retention, but also in supporting promotion. The research points out that employees who have been mentored have higher salaries, get more promotions, and have a higher level of satisfaction in their careers (Harrington and Marshall, 2014). It also enhances scholarly productivity and successful promotion and tenure.…”
Section: Benefitsmentioning
confidence: 99%
“…It also helps in the adoption and cultivation of organizational values and goals, which in turn fosters positive attitudes. Employees are more likely to be successful when they understand the organizational culture (Harrington and Marshall, 2014). It also provides psychosocial support as the mentor can be a role model for mentees, which requires a strong commitment on the part of the mentor to create an environment that fosters this positive experience (Goodsett and Walsh, 2015).…”
Section: Benefitsmentioning
confidence: 99%
“…A focus group study found that the experience promotes mentors' self-awareness and reflection on their own practice (Lacy & Copeland, 2013). A survey among academic libraries in Canada revealed that librarians perceived mentorship activities valuable for career guidance and psychosocial support but not so much as a means of expertise transfer (Harrington & Marshall, 2014). In a university library in the state of Virginia, the experience of running a mentorship program for library school students and new recruits provided the mentors a sense of accomplishment and satisfaction.…”
Section: Mentorshipmentioning
confidence: 99%
“…While there are libraries actively engaged in strategically integrated internal knowledge management processes (Balagué et al, 2015(Balagué et al, , 2016, it is clear that most libraries have not adopted such processes. Relatively recent studies indicate that, at least in academic libraries, there is an overall lack of attention to retention in general (Strothmann and Ohler, 2011) and to specific programs that might aid in retention (Harrington and Marshall, 2014). Without CLO-like oversight of retention initiatives, libraries will continue to face the challenges associated with engaging and retaining employees common to all organizations including libraries (Markgren et al, 2007;Deloitte, 2016).…”
Section: Retentionmentioning
confidence: 99%